OPTIMAL EXERCISE INTENSITY ESTIMATION METHOD, TRAINING METHOD, EXERCISE INSTRUCTION DEVICE, AND OPTIMAL EXERCISE INTENSITY ESTIMATION SYSTEM - UETO, Yuri; ABE, Masatsugu (2024)
An object is to provide a method, and a system, for estimating optimal exercise intensity, a training method that involves exercising at the optimal exercise intensity estimated by this estimation method, as well as an exercise instruction device, and an exercise instruction system, capable of indicating a workload for attaining an individual's optimal exercise intensity. As a solution, a method for estimating optimal exercise intensity is provided, which comprises: a step to give a ramped load to a subject so as to obtain a value of blood oxygen concentration (SpO2) at each [predetermined] different workload, which is measured over a range that overlaps at least a part of 96 to 100%; and a step to determine a starting point of decline at which the measured value of blood oxygen concentration starts to show a declining trend as the workload increases; wherein the workload at the starting point of decline is estimated as an optimal exercise intensity for the subject.